2023
DOI: 10.1101/2023.09.14.23295586
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A cluster-randomized trial of client and provider-directed financial interventions to align incentives with appropriate case management in retail medicine outlets: results of the TESTsmART Trial in western Kenya

J. Laktabai,
E. Kimachas,
J. Kipkoech
et al.

Abstract: ACTs are responsible for a substantial proportion of the global reduction in malaria mortality over the last ten years. These reductions would not have been possible without publicly-funded subsidies making these drugs accessible and affordable in the private sector. However, inexpensive ACTs available in retail outlets have contributed substantially to their overconsumption. We test an innovative, scalable, and sustainable strategy to target ACT subsidies to clients with a confirmatory diagnosis. We supported… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…This study is linked to a similar cluster randomized controlled trial in the contrasting rural study site of the region around Webuye in western Kenya. These results are pending publication elsewhere [8]. Full details of the study design were previously reported in Woolsey et al [9, 10].…”
Section: Methodsmentioning
confidence: 91%
“…This study is linked to a similar cluster randomized controlled trial in the contrasting rural study site of the region around Webuye in western Kenya. These results are pending publication elsewhere [8]. Full details of the study design were previously reported in Woolsey et al [9, 10].…”
Section: Methodsmentioning
confidence: 91%